Impact of Abusive Supervision on Affective Commitment with the Moderating Role of Self-Control Capacity of Non-Managerial Employees in Apparel Industry: A Sri Lankan Perspective - S. Sivapathasundharam; P. Jayasekara (Kelaniya Journal of Management)
The study examines the influence of abusive supervision on affective commitment among non-managerial employees in the Sri Lankan apparel industry, focusing on the potential moderating role of self-control capacity. Data was gathered from 257 randomly selected non-managerial employees from three knitted export organizations in Sri Lanka using self-administered questionnaires. The data were analyzed using SPSS 23. The results indicate a significant negative impact of abusive supervision on affective commitment, consistent with previous research findings. However, the study found that the moderating effect of self-control capacity was not statistically significant. This suggests that even though non-managerial employees may possess a moderate level of self-control capacity, it may not be adequate to mitigate the impact of abusive supervision on affective commitment. These findings highlight the critical necessity for organizations within the Sri Lankan apparel industry to address abusive supervision behaviours and to implement strategies aimed at enhancing employee retention in organizations.